Performance Test of 1500 cc Fuel Motorcycle Using Pertalite – Bioethanol Mixture Fuel on Exhaust Gas - Nelson Manurung; Muhammad Anhar Pulungan; Billy Christian Manurung; Enzo W. B Siahaan; Sihar Siahaan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
The increasing world oil prices followed by the increasing demand for fossil fuels as well as the issue of the energy crisis and global warming which demands a better level of environmental quality have encouraged the government to take good policies in overcoming them. Currently the world has been thinking about alternative energy that can be used for diesel or otto motors. One of the alternative fuels developed is alcohol fuel. Alcohol is a type of hydrocarbon in which one of the hydrogen atoms is replaced by the hydroxyl radical OH. Many agricultural products in Indo-nesia have the potential to be developed as bioethanol. In this study, the effect of adding bioethanol on pertalite fuel will be studied. This is because pertalite is a fuel that is in accordance with the demands of automotive needs and developments. This study aims to determine the comparison of power, torque, and air-fuel ratio as well as to determine the comparison of the content of exhaust gas compounds tested on the Toyota Vios Limo 1500CC car using pertalite (E0) fuel, 10% pertalite-bioethanol mixture (E10). and 15% (E15), 20% (E20). The test results obtained that the calorific value of Pertalite fuel is 49411.98 kJ/kg, 10% gasohol has a value of 46764.82 kJ/kg, 15% gasohol has a value of 44262.82 kJ/kg, and then 20% gasohol has a val-ue of 45735.42 kJ/kg. The test results obtained an average torque and power per-formance of 10% gasohol fuel of 109.09 Nm and 71.73 HP. The highest air-fuel ratio in fuel but the table shows the highest air-fuel ratio in 15% gasohol fuel is 15.46 and then the lowest air-fuel ratio in 10% gasohol fuel is 11.58. Exhaust emis-sion levels for each compound tested for each fuel are still below the standard vehicle exhaust emission thresholds set by Toyota and the environmental agency.